2016
DOI: 10.1016/j.jvs.2016.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vein harvest does not negatively affect patency of great saphenous vein lower extremity bypass

Abstract: In experienced hands, EVH is associated with a significant decrease in wound complications with similar graft patency, reintervention rates, and limb salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
12
1
2
Order By: Relevance
“… 10 20 Similar outcomes have been reported when the LSV had been harvested by EVH for lower limb vascular procedures. 21 In the current study, only a small percentage of patients post-CABG had either an ischaemic event or evidence of blocked grafts on angiography: 2.4% (1/41) for EVH and 2.8% (1/36) for OVH.…”
Section: Discussionmentioning
confidence: 47%
“… 10 20 Similar outcomes have been reported when the LSV had been harvested by EVH for lower limb vascular procedures. 21 In the current study, only a small percentage of patients post-CABG had either an ischaemic event or evidence of blocked grafts on angiography: 2.4% (1/41) for EVH and 2.8% (1/36) for OVH.…”
Section: Discussionmentioning
confidence: 47%
“…Recent literature, including our own experience, examining the use of EVH in lower extremity bypass reports favorable wound complication rates and decreased length of stay, readmission rates, and cost compared with open vein harvest. 8,[16][17][18][19][20][21][22][23][24] These benefits, however, have come at the cost of decreased primary patency rates with EVH compared with OVH. 23,24 A possible mechanism for the decreased patency rates with EVH is increased vein handling leading to injury.…”
mentioning
confidence: 99%
“…However, recent data, including results from Teixeira et al 13 examining the VQI database during a 10-year period with >5000 patients, showed no association between vein harvest technique and the development of surgical site infection. 26 However, VQI data are limited to in-hospital events, and late wound infections may not be captured completely in this data set. Regardless, studies have frequently demonstrated lower rates of infection with EVH, including early data, 27 leading to its institution by groups for high-risk patients.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%